PENGEMBANGAN BAHAN AJAR KOMIK TERINTEGRASI ISLAM PADA MATERI HAKIKAT ILMU KIMIA - Suprianingsih, Nelis; Yenti, Elvi; Kurniawati, Yenni (Journal of Chemistry Education and Integration, 2022)
Abstract The design of Islamic integrated teaching materials in chemistry subjects is an important effort to increase and grow the awareness of students from intellectual, emotional and spiritual aspects. This study aims to design Islamic integrated comics teaching materials on the nature of chemistry, and determine the level of validity and practicality as well as student responses to the designed comics teaching materials. The type of research used is Research and Development (R&D) with the Borg and Gall development model which includes 5 stages carried out namely information gathering, planning, development, testing, and final revision. The subjects of this research are material experts, Islamic religious experts, media experts, chemistry teachers and students of class X Science 1, and the object of research is an Islamic integrated comic on the material nature of chemistry. Comics are said to be feasible if they are valid and practical, with the percentage of validity obtained from material experts of 92.08% (very valid), the percentage of validity of Islamic religious experts is 76% (valid), the percentage of validity from media experts is 89.52% (very valid), the percentage of practicality obtained from chemistry teachers is 86.81% (very practical), and 80% of students give a very good response to the overall comic design. These results identify that Islamic integrated comics on the material nature of chemistry are valid and practical, further research is needed to test product productivity. Keywords : Teaching Materials, Comics, The Nature of Chemistry, Integrated Islam.